2010
DOI: 10.1007/s11192-010-0271-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact evaluation of the voluntary early retirement policy on research and technology outputs of the faculties of science in Morocco

Abstract: Scientometric indicators or science metrics, conventional and derived ones, are used in ex-post evaluating of a government policy with impact on research system. Publications, citations, h-index, Glänzel model, and patents are applied in both micro and meso levels. This provides useful insight into the impact of the voluntary early retirement policy on research and technological outputs of the faculties of science in Morocco and consequently on the overall Morocco's research system. The use of these metrics sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Indeed, for example, Schubert and Glänzel ( 2007 ) found, for γ , the estimates 0.73 and 0.76, in a study on the h -index for journals, for two different sets of journals, while Csajbók et al ( 2007 ) found an estimate of γ of 0.93 in a macro-level analysis of the h -index for countries. Instead, other authors, among them Annibaldi et al ( 2010 ), Bouabid et al ( 2011 ) and Zhao et al ( 2014 ), have found values of around 0.8. In quite different contexts (partnership ability and h -index for networks) Schubert ( 2012 ) and Schubert et al ( 2009 ) have estimated the parameter γ of the model , obtaining values within the range 0.6–0.96.…”
Section: Methodsmentioning
confidence: 94%
“…Indeed, for example, Schubert and Glänzel ( 2007 ) found, for γ , the estimates 0.73 and 0.76, in a study on the h -index for journals, for two different sets of journals, while Csajbók et al ( 2007 ) found an estimate of γ of 0.93 in a macro-level analysis of the h -index for countries. Instead, other authors, among them Annibaldi et al ( 2010 ), Bouabid et al ( 2011 ) and Zhao et al ( 2014 ), have found values of around 0.8. In quite different contexts (partnership ability and h -index for networks) Schubert ( 2012 ) and Schubert et al ( 2009 ) have estimated the parameter γ of the model , obtaining values within the range 0.6–0.96.…”
Section: Methodsmentioning
confidence: 94%